The Inability of South Africa to Comprehend the Foreign Policy Apparatus and the Political Climate in the United States of America Correctly - Eksteen, Riaan (Scientia Militaria - South African Journal of Military Studies, 2025)
This article reports on South African foreign policy in the context of the changing dynamics of Pres. Donald Trump’s second term of office. It contends that South Africa has faced difficulties in adjusting to these developments and new foreign policy imperatives. The foreign policy of a country is profoundly influenced by its domestic realities. The Trump administration has implemented substantial changes in the foreign policy of the United States of America, marked by assertive negotiating strategies and an emphasis on economic, national interest and security priorities, which have compromised international partnerships. Trump’s “America First” strategy has led to a withdrawal from enduring global obligations, affecting ties with other countries, particularly South Africa. Relations between the two countries were further exacerbated by limited understanding by South Africa of the political context of the United States. The disparity between the South African foreign policy initiatives and the realities of United States internal politics has caused misinterpretations of United States intentions. In March 2025, the South African ambassador was declared persona non grata by the United States, and the imposition of tariffs on South Africa further strained relations between the two countries. Sanctions being legislated by Congress remain a distinct possibility and would carry inordinate consequences for South Africa. Although the relationship between South Africa and the United States is anticipated to develop, the present circumstances remain ambiguous. The current research highlights the crucial importance of informed participation and a thorough understanding of the prevailing political processes.